Contributions and Limitations of National Cervical Cancer Screening Program in Korea: A Retrospective Observational Study - Jung Hyun Lee, MPH; Hyeongsu Kim, M.D., PhD; Heejung Choi, RN, Ph.D; Hyoseon Jeong, Ph.D; Young Ko, RN, Ph.D; Seung-Hyuk Shim, M.D; Eunjoo Lee, Ph.D; Su Hyun Chae, M.D (Elsevier, 2018)
Summary: Purpose: The purpose of this study was to evaluate the contributions and limitations of the cervical cancer screening test with accuracy in Korea. Methods: This was a retrospective observational study. The study population consisted of all participants who underwent cervical cancer screening test from 2009 to 2014. The data were obtained from National Health Information Database (NHID) which represents medical use records of most Koreans. As the indices for contributions and limitations of the screening test, crude detection rate, incidence rate of interval cancer, sensitivity, specificity, and positive predictive value were used. Results: The crude detection rate of screening test per 100,000 participants increased from 100.7 in 2009 to 102.1 in 2014. The incidence rate of interval cancer per 100,000 negatives decreased from 13.0 in 2009 to 10.2 in 2014. The sensitivities of screening test were 88.7% in 2009 and 91.2% in 2014, and the specificities were 98.5% in 2009 and 97.7% in 2014. The positive predictive value of screening decreased from 6.2% in 2009 to 4.3% in 2014. Conclusion: The Korean national cervical cancer screening program has improved in accuracy and has contributed to detection of early stage of cervical cancer over the years. Along with efforts to promote participation in cancer screening programs, quality control over the screening program should be enhanced. Keywords: carcinoma in situ, early detection of cancer, Papanicolaou test, sensitivity and specificity, uterine cervical neoplasms